2003
DOI: 10.1590/s0101-20612003000300008
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia para elaboração de fermentado de cajá (Spondias mombin L.)

Abstract: A produção do vinho passou de somente arte para arte com embasamento científico, ampliando-se as pesquisas em vitivinicultura [12]. Toda a tecnologia de produção do vinho é conhecida e cada vez mais estudada, buscando-se a melhor qualidade e a maior produtividade [37]. A vitivinicultura tem sido difundida no Brasil com vistas a um crescimento de produção e valorização do vinho nacional. Como a uva, várias outras frutas podem ser utilizadas para a formulação de mostos que podem, posteriormente, ser submetidos à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1
15

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 9 publications
4
31
1
15
Order By: Relevance
“…These values stay above the acidity found for the cajá wine (2.0 g/L), assessed by Dias, Schwan, and Lima (2003) and below the results found by Corazza et al (2001) for the acidity of the orange wine (8.1 g/L).…”
Section: Resultscontrasting
confidence: 62%
“…These values stay above the acidity found for the cajá wine (2.0 g/L), assessed by Dias, Schwan, and Lima (2003) and below the results found by Corazza et al (2001) for the acidity of the orange wine (8.1 g/L).…”
Section: Resultscontrasting
confidence: 62%
“…This includes alcoholic and acetic, as well as various other types of fermentation. Recently some research results on the fermentation of guava and banana (Bhatt et al, 1997), onion (Hirouchi et al, 2000), kiwi (Bertolini et al, 2001), orange (Corazza et al, 2001) and cajá (spondias mombin L.) (Dias et al, 2003) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In a kinetic study with fermented apple (Souza et al, 2011), populations affected by the CA-11 yeast at the end of the fermentation process were considered high (10 8 cells mL -1 ), showing CA-11 yeast efficiency to achieve high viable cell populations in the fermentation process, which was also observed in this study. Initial value was close to 10 7 cells mL -1 , which is the optimal concentration to initiate fruit must fermentation (Dias et al, 2003).…”
Section: Resultsmentioning
confidence: 67%
“…After decantation, the solution underwent vacuum filtration in a Büchner flask, 1000 mL, where a Büchner funnel was attached and cellulose filter was used (Dias et al 2003;Dias et al, 2007).…”
Section: Fermented Persimmon Preparationmentioning
confidence: 99%
See 1 more Smart Citation